Characterizing dropped head syndrome across neurologic disorders, the hidden epidemic of dropped head syndrome - Gómez-Piña, Juan José (International Journal of Research in Medical Sciences, 2023)
Background: Dropped head syndrome (DHS) usually characterizes neuromuscular disorders, however, is present in other neurological disorders as Parkinson’s disease. Despite being a syndrome seen in the clinic, it’s uncommon reported in the literature. Methods: This retrospective study reviewed electronic medical records of patients hospitalized with neurological disorders from 2018-2022 in a single center. Of 1359 charts screened, 134 patients were confirmed to have co-occurring DHS based on documented neck extensor weakness and an associated neurological condition. Strict inclusion criteria were applied to ensure all included patients had a confirmed neurological disorder and physical exam findings consistent with DHS. Results: Of 1359 patients hospitalized with neurological disorders, only 134 (0.96%) had co-occurring DHS. The cohort included 69 females (ages 24-79 years) and 65 males (25-87 years). The most prevalent neurological diagnoses linked to DHS were Parkinson’s disease, chronic inflammatory demyelinating polyneuropathy, and myasthenia gravis. Less common associations were multiple system atrophy and Alzheimer’s disease. The observed DHS prevalence may underestimate the true rate, highlighting the need for enhanced awareness and assessment. Conclusions: Despite a high prevalence of neurological disorders like Parkinson’s disease, chronic inflammatory demyelinating polyneuropathy, and myasthenia gravis at our hospital, dropped head syndrome remained uncommon, affecting only 134 out of 1359 (0.96%) hospitalized neurological patients. DHS showed no sex predilection but predominantly affected older individuals, likely reflective of age-related sarcopenia. This study provides initial data on the prevalence of DHS across different neurologic conditions and underscores the need for early detection to enable timely surgical and nonsurgical interventions. Further research is warranted to elucidate the risk factors and optimal management strategies for this enigmatic condition.